Inhibition of microRNA-21 via locked nucleic acid-anti-miR suppressed metastatic features of colorectal cancer cells through modulation of programmed cell death 4 - Reza Nedaeinia; Mohammadreza Sharifi; Amir Avan; Mohammad Kazemi; Abdolreza Nabinejad; Gordon A Ferns; Majid Ghayour-Mobarhan; Rasoul Salehi (Tumor Biology)
Colorectal cancer is among the most lethal of malignancies, due to its propensity to metastatic spread and multifactorial-chemoresistance. The latter property supports the need to identify novel therapeutic approaches for the treatment of colorectal cancer. MicroRNAs are endogenous non-coding small RNA molecules that function as post-transcriptional regulators of gene expression. Recently, programmed cell death 4 has been identified as a protein that increases during apoptosis. This gene is among the potential targets of miR-21 (OncomiR). Locked nucleic acid–modified oligonucleotides have recently emerged as a potential therapeutic option for targeting microRNAs. The aim of this study was to explore the functional role of locked nucleic acid-anti-miR-21 in the LS174T cell line in vitro and in vivo models. LS174T cells were treated with locked nucleic acid-anti-miR-21 for 24, 48, and 72 h in vitro. The expression of miR-21 and PDCD4 at messenger RNA (mRNA) level was evaluated by quantitative real-time polymerase chain reaction, while the protein level of PDCD4 was determined by Western blotting. Cell migratory behavior and the cluster-forming ability of cells were assessed before and after therapy. The disseminated tumor cells were assessed in the chick chorioallantoic membrane model by Alu quantitative polymerase chain reaction. Locked nucleic acid-anti-miR-21 was transfected successfully into the LS174T cells and inhibited the expression of miR-21. Locked nucleic acid-anti-miR-21 inhibited the migration and the number of cells forming clusters. Moreover, we found that locked nucleic acid-anti-miR-21 transfection was associated with a significant reduction in metastatic properties as assessed by the in ovo model. Our findings demonstrated the novel therapeutic potential of locked nucleic acid-anti-miR-21 in colon adenocarcinoma with high miR-21 expression.